Song varies with latitude, climate, and species richness in a Neotropical bird. (11th October 2021) - Silva-Jr, Edvaldo F; Diniz, Pedro; Macedo, Regina H
Abstract: Animals can encode information within acoustic signals, particularly, bird songs can be remarkably complex and can indicate individual identity and quality. Two main sets of hypotheses attempt to explain the evolution of increased birdsong complexity across large-scale geographic ranges: 1) larger acoustic space availability, and 2) greater sexual selection intensity, both of which would favor the evolution of more complex songs at higher latitudes, more seasonal and/or species-poor environments. However, few studies have assessed patterns of song complexity for birds with broad geographic ranges. Here, we determined patterns of song variation in the blue-black grassquit ( Volatinia jacarina ), considering metrics of song complexity, structure and performance. This Neotropical bird occurs from Mexico to Argentina and produces a monosyllabic song. Using recordings from online databases, we calculated song metrics, such as bandwidth, song rate, number of song components, and proportion of vibratos of this signal. We found that song features varied with latitude, climate seasonality, bird species richness, and hemisphere. However, contrary to theoretical predictions, complexity mostly decreased with latitude and greater seasonality, while it was positively correlated with bird species richness. Proportion of vibratos was positively correlated with latitude and seasonality, and may be a feature under sexual selection in this species. Overall, our results did not support the main hypotheses proposed as explanations for song complexity. Our findings also highlight that song complexity does not vary uniformly among songbirds and song parameters, and future studies encompassing more species should clarify patterns and drivers of song variation across broad geographic dimensions. Abstract : Elaborate traits, such as complex bird songs, can encode information about individual identity and quality as a mate. Although birdsong is a well-studied topic, few studies have investigated how song complexity varies geographically across large-scale regions. Using recordings from online databases, we show that a broadly distributed tropical bird, the blue-black grassquit, usually sings simpler songs at higher latitudes. We also found that songs were simpler in variable climates and/or in species-poor environments.